Three decades of neuroscience research using animal models of ADHD and ASD: a bibliometric analysis - Dougnon, Godfried; Matsui, Hideaki (Frontiers in Psychiatry, 2025)
IntroductionAttention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorders (ASD) are two increasingly prevalent neurodevelopmental disorders (NDDs), often accompanied by significant daily-life challenges. Animal models play a crucial role in studying these conditions, and recent advances have highlighted the potential of animal models such as mice, rat, zebrafish, Drosophila or Caenorhabditis elegans for investigating NDDs. However, despite growing interest, a complete understanding of these disorders has yet to be achieved. We believe that to properly address these NDDs, it is important to analyze the heterogeneity of ADHD and ASD research.MethodsThis study comprehensively analyzes ADHD and ASD-related scientific publications from January 1990 to December 2023 using data from the Web of Science (WoS), exploring trends in global research output, impact factors, citation metrics, the predominant use of animal models, the contribution of major countries and funding information.ResultsOut of the 10,844 papers from WoS, we curated 5,883 papers and identify mice and rat as the primarily used animal models, and a progressive use of zebrafish, Drosophila and C. elegans since the early 2000s. The countries conducting research on ADHD and ASD were principally the United States (3,059 articles), followed by China (487 articles), the United Kingdom (459 articles), Japan (440 articles), Germany (413 articles). We further show that impact factors and journal citations were relatively similar among the major publishing countries. Interestingly, key research funders were the National Institute of Health (NIH), the National Institute of Mental Health (NIMH), and the Japanese Ministry of Education Culture Sports Science and Technology (MEXT), making important contributions to their respective countries’ publications. Of note, Africa and Oceania have a lower volume of publication; however, our network analysis indicates a recent peak in research interest and ADHD/ASD awareness in some countries like Ghana or Portugal.ConclusionThe findings highlight significant advancements and collaborative efforts in ADHD and ASD research over the last three decades, underscoring the importance of international cooperation in addressing these complex neurodevelopmental disorders.